Case Study : The Boom Beverage Sdn Bhd / Muhammad Faiz Amin - Amin, Muhammad Faiz (2021)
This study is conduct based in The Boom Beverage Sdn Bhd that being establish by 3 founder that is Azri Zahier Azmi, Zaid Hurairah and Errwan Haddie Arshad in 2014. this study purpose it to learn and find out the process that The Boom Beverage Sdn Bhd has being through to be able to make their product go all around the world. this include knowing one of the founders and what his future goal they want to achieve from making a Hausboom drink.based on the founder and chief executive officer (CEO) Azri Zahier Azmi, he finds a need on making a premium, halal, carbonate beverage that made of real fruit that is getting popular in competitive global beverage market. as a Malaysian he finds that Malaysia is one of the countries that frequently held a halal food festival and want to be champion in halal food industry. This give him idea to make a Hausboom drink that is halal.Their targeted market has no limit, whether it a young generation or old generation. this is thanks to the product that not contains alcohol. but it more focus toward younger generation because its product is reflecting about lifestyle.